Odin observations of Antarctic nighttime NO densities in the mesosphere-lower thermosphere and observations of a lower NO layer - Sheese, P. (author); Strong, K. (author); Gattinger, R. (author); Llewellyn, E. (author); Urban, J. (author); Boone, C. (author); Smith, Anne (author) (Journal of Geophysical Research: Atmospheres, 2013)
The Optical Spectrograph and Infrared Imaging System (OSIRIS) on the Odin satellite currently has an eight-year dataset of nighttime Antarctic nitric oxide densities, [NO], in the mesosphere–lower thermosphere (MLT) region. In this work, the OSIRIS data are compared with a similar data set from the Sub-Millimeter Radiometer (SMR), also on the Odin satellite. Both of the Odin data sets are compared with twilight [NO] from the Atmospheric Chemistry Experiment-Fourier Transform Spectrometer (ACE-FTS) on the SciSat-I satellite. Direct comparisons of OSIRIS and SMR profiles show large differences, indicating that the individual [NO] profiles of one or both data sets may not be valid. However, when comparing averaged [NO], variations on timescales of weeks-years in all three data sets are in good agreement and correspond to the 27 day and 11 year solar cycles. The averaged OSIRIS values are typically 10% greater than SMR and 30% greater than ACE-FTS, which are within the estimated OSIRIS systematic uncertainties. These results suggest that the satellite-derived data sets can be used for determining polar-mean NO climatology and variations on timescales of weeks-years. The OSIRIS and SMR nighttime data sets show that the [NO] peak height in the MLT decreases throughout the autumn, from an altitude near or above 100 km to a minimum altitude ranging from 90 to 95 km around winter solstice. A similar decrease in [NO] peak height is observed in modeled NO climatology from the Specified Dynamics–Whole Atmosphere Community Climate Model (SD-WACCM), although the SD-WACCM climatology exhibits a decrease throughout autumn from 107 km down to 102 km. The results suggest that global climate models require more sophisticated auroral forcing simulations in order to reproduce observed NO variations in this region.